2014
DOI: 10.1186/2251-6581-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and total serum bilirubin levels among insulin sensitive and insulin resistant U.S. adults

Abstract: BackgroundTotal serum bilirubin has been identified as a novel biomarker for metabolic disease, with higher levels providing protection against metabolic disease. To our knowledge, only 3 studies, to date, have examined the association between physical activity and total serum bilirubin, with these studies reporting mixed findings. One potential reason for the mixed findings may be the exclusive use of self-report physical activity methodology. The purpose of this study was to examine the association between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…A more recent study confirmed these observations by examining why moderate-to-vigorous physical activity (MVPA) resulted in a significant increase in serum bilirubin in insulin-resistant subjects but not in insulin-sensitive subjects. The authors hypothesized that the observed increase in bilirubin in the insulin-resistant subjects could be due to a lower basal level of bilirubin, resulting in a more remarkable absolute change in bilirubin in response to MVPA [ 74 ]. The underlying rationale for this pattern of bilirubin change in response to different exercise volumes should be further explored to improve our understanding of the connection between insulin resistance and changing bilirubin levels.…”
Section: Ho-1 Bvra and Bilirubin As Inflammatory Mediatorsmentioning
confidence: 99%
“…A more recent study confirmed these observations by examining why moderate-to-vigorous physical activity (MVPA) resulted in a significant increase in serum bilirubin in insulin-resistant subjects but not in insulin-sensitive subjects. The authors hypothesized that the observed increase in bilirubin in the insulin-resistant subjects could be due to a lower basal level of bilirubin, resulting in a more remarkable absolute change in bilirubin in response to MVPA [ 74 ]. The underlying rationale for this pattern of bilirubin change in response to different exercise volumes should be further explored to improve our understanding of the connection between insulin resistance and changing bilirubin levels.…”
Section: Ho-1 Bvra and Bilirubin As Inflammatory Mediatorsmentioning
confidence: 99%
“…Although limited in examination, smoking is inversely associated with bilirubin, 23,24 while physical activity is positively associated with bilirubin. [24][25][26][27] Additionally, the effect of other health-enhancing behaviors (eg, diet) on bilirubin levels is unclear. It is plausible to suggest that adequate consumption of flavonoid-rich fruits and vegetables may be associated with bilirubin, given their influence on inflammation, 28 markers of CV disease, 29 and more importantly, their ability to modulate enzymes (eg, uridine 5 0 -diphosphoglucuronosyltransferases) that influence bilirubin levels.…”
Section: Introductionmentioning
confidence: 99%
“…The fasting serum insulin (FINS) was determined by the ELISA kit. The insulin resistance index (HOMA-IR) was calculated as FBG (mmol/L) × FINS ( μ U/mL)/22.5, IR was defined as HOMA-IR > 2.6 [2527], and the homeostasis model assessment- β (HOMA- β ) was calculated based on the following formula: HOMA- β = [(20 ∗ FINS)/(FBG − 3.5)] [28]. All parameters were obtained according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%